Enhancements to the USGS Landsat Level 2 surface temperature and emissivity product for Collection 3 reprocessing - Saeed Arab; Chase Mueller; Christopher J. Crawford; Danika Wellington; Ray Dittmeier; Glynn Hulley; Aaron Gerace; Calli Jenkerson; Simon Hook; Amirhossein Hassanzadeh; Rehman Eon; Cody Anderson; et al. (Remote Sensing of Environment, 2026)

Biomass and composition of Atlantic menhaden schools in winter on the continental shelf offshore of New Jersey: Application of a novel hydroacoustic survey with midwater trawl sampling - Geneviève Nesslage; James Gartland; Robert J. Latour; Christopher Gurshin; Dong Liang; Dustin Gregg; Stefan Axelsson; Leif Axelsson; Wayne Reichle; Jeff Kaelin; J. Michael Jech; Ray Mroch; et al. (Fisheries Research, 2026)

Manistee, a new Round-White Early to Mid-Season Maturing Potato Variety with Excellent Long-Term Storage Potential - David S. Douches; Joseph J. Coombs; William L. Behling; Ray Hammerschmidt; Greg E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2025)
Manistee is a round white chip-processing potato ( Solanum tuberosum ) variety developed for long-term storage. Evaluated as MSL292-A, Manistee is a selection from a cross between Snowden and the chip-processing breeding line MSH098-2. The tubers of Manistee are compressed, round with shallow eyes and early to mid-season maturity. Field testing and on-farm trials show that this variety has high yield potential with specific gravity comparable to Snowden and similar to better tolerance to blackspot bruise. Manistee was formally released in 2013 and has demonstrated reliable and excellent long-term storage chip-processing quality up to eight months post-harvest which extends the chip-processing storage season beyond Snowden. Furthermore, preliminary studies with Manistee, Snowden, Lamoka and Pike tuber disks demonstrated that Manistee started the wound healing process faster than Lamoka and Pike and slightly faster than Snowden which supports observations of stable and reliable commercial storage of the tubers for chip-processing.

That's So Last Season: Unraveling the Genomic Consequences of Fur Farming in Arctic Foxes ( Vulpes lagopus ) - Christopher A. Cockerill; J. Camilo Chacón‐Duque; Nora Bergfeldt; Johanna von Seth; Gabriella Björklund; Malin Hasselgren; Johan Wallén; Anders Angerbjörn; Eva Fuglei; Ester Rut Unnsteinsdottir; Paula White; Gustaf Samelius; et al. (Molecular Ecology, 2025)
Humans have relied on animal fur for centuries, yet fur farming only began recently during the mid‐19th Century. Little is known about this incipient domestication or the genomic processes involved. Domestication may involve founder effects, population bottlenecks and low population size, which, when combined with intense artificial selection, lead to inbreeding, a limited gene pool and reduced fitness. The arctic fox ( Vulpes lagopus ) has been farmed intensively since the early 1900s and has been artificially selected for economic phenotypes. We investigated the origin of these lineages and the genomic consequences of intensive farming by comparing the genomes of farmed and wild arctic foxes from across their range. Our research indicates recent inbreeding through long Runs of Homozygosity and reduced genomic variation in farmed foxes relative to their respective wild populations. We identified a coastal ecotype origin for all Fennoscandian farmed arctic foxes, aligning them phylogenetically with the wild Icelandic population, a geographically isolated and phenotypically distinct coastal lineage. The depleted genome‐wide heterozygosity and increased recent inbreeding in farmed fox lineages is consistent with a heavy consequence of domestication, shedding light on the demographic history and genomic consequences of human manipulation. We highlight the need for increased genomic investigations into fur farm populations to understand the incipient domestication process and uncover the cost of intense farming. The genomic consequences of domestication must be considered in the management of fur farms, with actionable steps needed to prevent descendants of escaped farmed foxes from polluting the gene pool in the wild through introgression.

The Wolverine Project: Evaluating Cumulative Effects Within the Land of Ktunaxa Using the One Heart Method - Nikki Heim; Ryan MacDonald; Christopher Horsethief; Chad Luke; Michael Proctor; Marlene Machmer; Vi Birdstone; Ray Warden; Curtis Wullum; Rachel Plewes; Matthew Chernos; Matt Carlson (Environmental Management, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Magnetic resonance imaging of a stream of bubbles injected into liquid suspensions - Alireza Bordbar; Wasif Zia; Janine Birnbaum; Javad Omidi; Ray F. Lee; Einat Lev; Christopher M. Boyce (Chemical Engineering Journal, 2024)

Reconstructing 120 years of climate change impacts on Joshua tree flowering - Jeremy B. Yoder; Ana Karina Andrade; Lesley A. DeFalco; Todd C. Esque; Colin J. Carlson; Daniel F. Shryock; Ray Yeager; Christopher I. Smith (Ecology Letters, 2024)
Quantifying how global change impacts wild populations remains challenging, especially for species poorly represented by systematic datasets. Here, we infer climate change effects on masting by Joshua trees ( Yucca brevifolia and Y. jaegeriana ), keystone perennials of the Mojave Desert, from 15 years of crowdsourced observations. We annotated phenophase in 10,212 geo‐referenced images of Joshua trees on the iNaturalist crowdsourcing platform, and used them to train machine learning models predicting flowering from annual weather records. Hindcasting to 1900 with a trained model successfully recovers flowering events in independent historical records and reveals a slightly rising frequency of conditions supporting flowering since the early 20th Century. This reflects increased variation in annual precipitation, which drives masting events in wet years—but also increasing temperatures and drought stress, which may have net negative impacts on recruitment. Our findings reaffirm the value of crowdsourcing for understanding climate change impacts on biodiversity.

Testing of tissue specimens obtained from SARS-CoV-2 nasopharyngeal swab-positive donors - Melissa A. Greenwald; Shabnam Namin; Jan Zajdowicz; Alyce Linthurst Jones; Linda Fritts; Matthew J. Kuehnert; Christopher J. Miller; Gregory Ray (Cell and Tissue Banking, 2024)
Risk for transmission of SARS-CoV-2 through allogeneic human tissue transplantation is unknown. To further evaluate the risk of virus transmission, tissues were obtained from deceased donors who had tested positive for SARS-CoV-2 RNA via nasopharyngeal swab. This study evaluated an array of human tissues recovered for transplantation, including bone, tendon, skin, fascia lata, vascular tissues, and heart valves. Tissue samples and plasma or serum samples, if available, were tested for viral RNA (vRNA) using a real time PCR system for the presence of virus RNA. All samples were tested in quadruplicate for both subgenomic (sgRNA) and genomic (gRNA) RNA encoding the SARS-CoV-2 nucleocapsid gene. Amplification of a cellular housekeeping gene served as the positive control for every sample. A total of 47 tissue samples from 17 donors were tested for SARS-CoV-2 RNA. Four donors had plasma or serum available for paired testing. SARS-CoV-2 RNA was not detected from any tissue or plasma/serum sample tested. Based on these findings, risk of transmission through the transplantation of tissue types studied from SARS-CoV-2 infected donors is likely to be low.

Evaluating the Development and Application of Stand Density Index for the Management of Complex and Adaptive Forests - Emmerson Chivhenge; David G. Ray; Aaron R. Weiskittel; Christopher W. Woodall; Anthony W. D’Amato (Current Forestry Reports, 2024)

Assessing parallel path cooling tower performance via artificial neural networks - Christopher Katinas; Brian d'Entremont; William Ray; Michael Willis; Thomas Reichardt (Annals of Nuclear Energy, 2023)

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Rendered materials partly substitute inorganic nitrogen fertilizers and improve nitrogen recovery in maize production system - Bhupinder Singh Jatana; Christopher Ray; Christopher Kitchens; Patrick Gerard; Nishanth Tharayil (Nutrient Cycling in Agroecosystems, 2022)

A history and evaluation of catch‐only stock assessment models - Daniel Ovando; Christopher M. Free; Olaf P. Jensen; Ray Hilborn (Fish and Fisheries, 2022)
Understanding the status of fish stocks is a critical step in ensuring the ecological and economic sustainability of marine ecosystems. However, at least half of global catch and a vast majority of global fisheries lack formal stock assessments, largely due to a lack of sufficient data. Catch data, loosely referring to any catch records be it inclusive of discards or not, are the only type of fishery data available across a wide range of fisheries at a global scale. This has given rise to a long list of so‐called “catch‐only” models, intended to estimate aspects of stock status based primarily on characteristics of a fishery's catch history. In this paper, we review the history, performance and potential of “catch‐only” models to estimate stock biomass status. While individual catch‐only models often report good performance, repeated efforts to examine the performance of these models have consistently found them to be imprecise and biased when applied to new data‐limited fisheries. We demonstrate that a large reason for this is the simple lack of information on stock status contained in the shape of a catch history alone. Off‐the‐shelf use of catch‐only models can lead to poor and biased estimates of stock status, potentially hindering efforts at effective management.

Piscine mycobacteriosis in the ornamental fish trade in Trinidad and Tobago - Ayanna Carla N. Phillips Savage; Lemar Blake; Rod Suepaul; O’Shane McHugh; Ray Rodgers; Calvern Thomas; Christopher Oura; Esteban Soto (Journal of Fish Diseases, 2022)
The freshwater ornamental fish trade represents a major contributor to the livelihoods of many producers in Trinidad and Tobago, with stocks destined for local, regional and international markets. A review of clinical cases presented to the Aquatic Animal Health Unit at the University of the West Indies, School of Veterinary Medicine for the period September 2010 to December 2012 suggested that piscine mycobacteriosis may be widespread throughout the local ornamental fish industry. Thus, to determine the prevalence of mycobacteriosis in ornamental fish sold in pet stores, a total of 122 specimens were sourced from 24 retail suppliers across Trinidad. Fish were killed and internal organs were examined for lesions suggestive of granulomas. All wet‐mount slides were acid‐fast stained, regardless of the presence or absence of observed granuloma‐like lesions. Histological analysis was performed on one randomly selected whole specimen from each facility. Mycobacterium sp. was identified using real‐time PCR detecting the 16S rRNA gene in tissue samples. Associations between parasitism, facility biosecurity and presence of positive animals were determined. The prevalence of Mycobacterium sp. infection was 61 ± 7% (74/122), with positive specimens being acquired from 54.2% (13/24) of facilities examined. Further, 100% of facilities did not employ optimum biosecurity measures.

Disorders of Tetrahydrobiopterin Metabolism: Experience from South India - Somdattaa Ray; Hansashree Padmanabha; Vykuntaraju K. Gowda; Rohan Mahale; Rita Christopher; Shruthy Sreedharan; Debjyoti Dhar; Mahesh Kamate; Madhu Nagappa; Maya Bhat; Rammurthy Anjanappa; Gautham Arunachal; et al. (Metabolic Brain Disease, 2022)

Promises and pitfalls of digital knowledge exchange resulting from the COVID-19 pandemic - Vivian M. Nguyen; Christina Bell; Valerie Berseth; Christopher Cvitanovic; Ray Darwent; Matthew Falconer; Jenna Hutchen; Tyreen Kapoor; Nicole Klenk; Nathan Young (Socio-Ecological Practice Research, 2021)

Assessing the population‐level conservation effects of marine protected areas - Daniel Ovando; Jennifer E. Caselle; Christopher Costello; Olivier Deschenes; Steven D. Gaines; Ray Hilborn; Owen Liu (Conservation Biology, 2021)
Marine protected areas (MPAs) cover 3–7% of the world's ocean, and international organizations call for 30% coverage by 2030. Although numerous studies show that MPAs produce conservation benefits inside their borders, many MPAs are also justified on the grounds that they confer conservation benefits to the connected populations that span beyond their borders. A network of MPAs covering roughly 20% of the Channel Islands National Marine Sanctuary was established in 2003, with a goal of providing regional conservation and fishery benefits. We used a spatially explicit bioeconomic simulation model and a Bayesian difference‐in‐difference regression to examine the conditions under which MPAs can provide population‐level conservation benefits inside and outside their borders and to assess evidence of those benefits in the Channel Islands. As of 2017, we estimated that biomass densities of targeted fin‐fish had a median value 81% higher (90% credible interval: 23–148) inside the Channel Island MPAs than outside. However, we found no clear effect of these MPAs on mean total biomass densities at the population level: estimated median effect was –7% (90% credible interval: –31 to 23) from 2015 to 2017. Our simulation model showed that effect sizes of MPAs of

Evaluating impacts of forage fish abundance on marine predators - Christopher M. Free; Olaf P. Jensen; Ray Hilborn (Conservation Biology, 2021)
Forage fish—small, low trophic level, pelagic fish such as herrings, sardines, and anchovies—are important prey species in marine ecosystems and also support large commercial fisheries. In many parts of the world, forage fish fisheries are managed using precautionary principles that target catch limits below the maximum sustainable yield. However, there are increasing calls to further limit forage fish catch to safeguard their fish, seabird, and marine mammal predators. The effectiveness of these extra‐precautionary regulations, which assume that increasing prey abundance increases predator productivity, are under debate. In this study, we used prey‐linked population models to measure the influence of forage fish abundance on the population growth rates of 45 marine predator populations representing 32 fish, seabird, and mammal species from 5 regions around the world. We used simulated data to confirm the ability of the statistical model to accurately detect prey influences under varying levels of influence strength and process variability. Our results indicate that predator productivity was rarely influenced by the abundance of their forage fish prey. Only 6 predator populations (13% of the total) were positively influenced by increasing prey abundance and the model exhibited high power to detect prey influences when they existed. These results suggest that additional limitation of forage fish harvest to levels well below sustainable yields would rarely result in detectable increases in marine predator populations.

The evolution of hydrochemical and isotopic signatures from precipitation, surface water to groundwater in a typical karst watershed, Central Texas, USA - Lijun Tian; Yongli Gao; Guang Yang; Benjamin Schwartz; Binggui Cai; Guoliang Lei; Guitao Shi; Christopher Ray; Soeuth Sok; Erica Martinez; Yunxia Li; Haibin Wu (Isotopes in Environmental and Health Studies, 2021)

Not withering on the evolutionary vine: systematic revision of the Brown Vine Snake (Reptilia: Squamata: Oxybelis) from its northern distribution - Robert C. Jadin; Christopher Blair; Sarah A. Orlofske; Michael J. Jowers; Gilson A. Rivas; Laurie J. Vitt; Julie M. Ray; Eric N. Smith; John C. Murphy (Organisms Diversity & Evolution, 2020)

Regulating the nutrient release rates from proteinaceous agricultural byproducts using organic amendments and its effect on soil chemical and microbiological properties - Bhupinder Singh Jatana; Christopher Kitchens; Christopher Ray; Nishanth Tharayil (Biology and Fertility of Soils, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Early life social and ecological determinants of global DNA methylation in wild spotted hyenas - Zachary M. Laubach; Christopher D. Faulk; Dana C. Dolinoy; Luke Montrose; Tamara R. Jones; Donna Ray; Malit O. Pioon; Kay E. Holekamp (Molecular Ecology, 2019)
Environmental factors early in life can have lasting influence on the development and phenotypes of animals, but the underlying molecular modifications remain poorly understood. We examined cross‐sectional associations among early life socioecological factors and global DNA methylation in 293 wild spotted hyenas ( Crocuta crocuta ) in the Masai Mara National Reserve, Kenya, grouped according to three age classes (cub, subadult and adult). Explanatory variables of interest included annual maternal rank based on outcomes of dyadic agonistic interactions, litter size, wild ungulate prey density and anthropogenic disturbance in the year each hyena was born based on counts of illegal livestock in the Reserve. The dependent variable of interest was global DNA methylation, assessed via the LUminometric Methylation Assay, which provides a percentage methylation value calculated at CCGG sites across the genome. Among cubs, we observed approximately 2.75% higher CCGG methylation in offspring born to high‐ than low‐ranking mothers. Among cubs and subadults, higher anthropogenic disturbance corresponded with greater %CCGG methylation. In both cubs and adults, we found an inverse association between prey density measured before a hyena was 3 months old and %CCGG methylation. Our results suggest that maternal rank, anthropogenic disturbance and prey availability early in life are associated with later life global DNA methylation. Future studies are required to understand the extent to which these DNA methylation patterns relate to adult phenotypes and fitness outcomes.

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Effect of water on the fluorine and chlorine partitioning behavior between olivine and silicate melt - Bastian Joachim; André Stechern; Thomas Ludwig; Jürgen Konzett; Alison Pawley; Lorraine Ruzié-Hamilton; Patricia L. Clay; Ray Burgess; Christopher J. Ballentine (Contributions to Mineralogy and Petrology, 2017)

Metabarcoding and metabolome analyses of copepod grazing reveal feeding preference and linkage to metabolite classes in dynamic microbial plankton communities - Jessica L. Ray; Julia Althammer; Katrine S. Skaar; Paolo Simonelli; Aud Larsen; Diane Stoecker; Andrey Sazhin; Umer Z. Ijaz; Christopher Quince; Jens C. Nejstgaard; Marc Frischer; Georg Pohnert; et al. (Molecular Ecology, 2016)
In order to characterize copepod feeding in relation to microbial plankton community dynamics, we combined metabarcoding and metabolome analyses during a 22‐day seawater mesocosm experiment. Nutrient amendment of mesocosms promoted the development of haptophyte ( Phaeocystis pouchetii )‐ and diatom ( Skeletonema marinoi )‐dominated plankton communities in mesocosms, in which Calanus sp. copepods were incubated for 24 h in flow‐through chambers to allow access to prey particles ( P. pouchetii , were passively consumed or even negatively selected according to our indicator. Our analysis of the relationship between Calanus grazing ratios and intracellular metabolite profiles indicates the importance of carbohydrates and lipids in plankton succession and copepod–prey interactions. This molecular characterization of Calanus sp. grazing therefore provides new evidence for selective feeding in mixed plankton assemblages and corroborates previous findings that copepod grazing may be coupled to the developmental and metabolic stage of the entire prey community rather than to individual prey abundances.

Institutional factors and opportunities for adapting European forest management to climate change - Laura Bouriaud; Mariella Marzano; Manfred Lexer; Liviu Nichiforel; Christopher Reyer; Christian Temperli; Heli Peltola; Ché Elkin; Gabriel Duduman; Philip Taylor; Stephen Bathgate; Jose G. Borges; et al. (Regional Environmental Change, 2015)

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Evaluation of a combined macrophyte–epiphyte bioassay for assessing nutrient enrichment in the Portneuf River, Idaho, USA - Andrew M. Ray; Christopher A. Mebane; Flint Raben; Kathryn M. Irvine; Amy M. Marcarelli (Environmental Monitoring and Assessment, 2014)

Facilitating Return to Work for Injured and Ill Animal Agriculture Workers - Iris Anne Reyes; Nancy Bellendorf; Tami Meehan; Ron Wenger; Christopher Kadolph; Shaun Halstead; Andrea Mahnke; Bryan Weichelt; William Ray; Matthew Keifer (Journal of Agromedicine, 2014)

Impact of acamprosate on behavior and brain-derived neurotrophic factor: an open-label study in youth with fragile X syndrome - Craig A. Erickson; Logan K. Wink; Balmiki Ray; Maureen C. Early; Elizabeth Stiegelmeyer; Lauren Mathieu-Frasier; Vanessa Patrick; Debomoy K. Lahiri; Christopher J. McDougle (Psychopharmacology, 2013)

The muscarinic M1 receptor positive allosteric modulator PQCA improves cognitive measures in rat, cynomolgus macaque, and rhesus macaque - Jason M. Uslaner; Donnie Eddins; Vanita Puri; Christopher E. Cannon; Jane Sutcliffe; Chan Sing Chew; Michelle Pearson; Jeffrey A. Vivian; Ronald K. Chang; William J. Ray; Scott D. Kuduk; Marion Wittmann (Psychopharmacology, 2013)

The flow dynamics of an extremely large volume pyroclastic flow, the 2.08-Ma Cerro Galán Ignimbrite, NW Argentina, and comparison with other flow types - Ray A. F. Cas; Heather M. N. Wright; Christopher B. Folkes; Chiara Lesti; Massimiliano Porreca; Guido Giordano; Jose G. Viramonte (Bulletin of Volcanology, 2011)

Multiple tracers demonstrate distinct sources of dissolved organic matter to lakes of the Mackenzie Delta, western Canadian Arctic - Suzanne E. Tank; Lance F. W. Lesack; Jolie A. L. Gareis; Christopher L. Osburn; Ray H. Hesslein (Limnology and Oceanography, 2011)
Lakes of the Mackenzie Delta occur across a gradient that contains three clear end members: those that remain connected to river‐water channels throughout the summer; those that receive only brief inputs of river water during an annual spring flood but contain dense macrophyte stands; and those that experience significant permafrost thaw along their margins. We measured dissolved organic carbon (DOC) concentration, dissolved organic matter (DOM) absorption and fluorescence, and stable isotopes of DOM, DOM precursor materials, and bacteria to elucidate the importance of river water, macrophytes, and thermokarst as DOM sources to Mackenzie Delta lakes. Despite standing stocks of macrophyte C that are sevenfold to 12‐fold greater than those of total DOC, stable isotopes indicated that autochthonous sources contributed less than 15% to overall DOM in macrophyte‐rich lakes. Instead, fluorescence and absorption indicated that the moderate summertime increase in DOC concentration in macrophyte‐rich lakes was the result of infrequent flushing, while bacterial δ 13 C indicated rapid bacterial removal of autochthonous DOC from the water column. In thermokarst lakes, summertime increases in DOC concentration were substantial, and stable isotopes indicated that much of this increase came from C released as a result of thermokarst‐related processes. Our results indicate that these distinct sources of DOM to neighboring arctic Delta lakes may drive between‐lake differences in C cycling and energy flow. Rapidly assimilated macrophyte DOM should be an important contributor to microbial food webs in our study lakes. In contrast, the accumulation of thermokarst‐origin DOM allows for a significant role in physico‐chemistry but indicates a lesser contribution of this DOM to higher trophic levels.

Development and characterization of 16 microsatellite markers for the Louisiana pine snake, Pituophis ruthveni, and two congeners of conservation concern - Matthew A. Kwiatkowski; Christopher M. Somers; Ray G. Poulin; D. Craig Rudolph; Jessica Martino; Tracey D. Tuberville; Cris Hagen; Stacey L. Lance (Conservation Genetics Resources, 2010)

Adaptive response of equine intestinal Na+/glucose co-transporter (SGLT1) to an increase in dietary soluble carbohydrate - Jane Dyer; Miran Al-Rammahi; Louise Waterfall; Kieron S. H. Salmon; Ray J. Geor; Ludovic Bouré; G. Barrie Edwards; Christopher J. Proudman; Soraya P. Shirazi-Beechey (Pflügers Archiv - European Journal of Physiology, 2009)

Latent structure of facets of alcohol reinforcement from a behavioral economic demand curve - James MacKillop; James G. Murphy; Jennifer W. Tidey; Christopher W. Kahler; Lara A. Ray; Warren K. Bickel (Psychopharmacology, 2009)

Pharmacological effects of naltrexone and intravenous alcohol on craving for cigarettes among light smokers: a pilot study - Lara A. Ray; Robert Miranda; Christopher W. Kahler; Adam M. Leventhal; Peter M. Monti; Robert Swift; Kent E. Hutchison (Psychopharmacology, 2007)

A geminivirus-induced gene silencing system for gene function validation in cassava - Ismael B. F. Fofana; Abdourahamane Sangaré; Ray Collier; Christopher Taylor; Claude M. Fauquet (Plant Molecular Biology, 2004)

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

Stratification by CARD15 variant genotype in a genome-wide search for inflammatory bowel disease susceptibility loci - Sarah H. Shaw; Jochen Hampe; Ray White; Christopher G. Mathew; Mark E. Curran; Stefan Schreiber (Human Genetics, 2003)

Susceptibility of potato varieties and advanced breeding lines (Solanum tuberosum L.) toPhytophthora infestans (Mont.) de Bary in greenhouse screenings - David S. Douches; William W. Kirk; Kazimierz Jastrzebski; Christopher Long; Ray Hammerschmidt (American Journal of Potato Research, 1997)